The Power of Old Hats: Rediscovering Inosine-EpPCR to Create Starting Libraries for Whole-Cell-SELEX - Grigory Bolotnikov; Ann-Kathrin Kissmann; Daniel Gruber; Andreas Bellmann; Roger Hasler; Christoph Kleber; Wolfgang Knoll; Frank Rosenau (Biosensors, 2025)
Shaking off the forgetfulness towards the methodological power of inosine-mediated error-prone PCR (epPCR), this study reintroduces an often-underappreciated method as a considerably powerful approach for generating aptamer libraries from a single decameric ATCG-repeat-oligonucleotide. The aim was to demonstrate that this simple way of creating sequence diversity was suitable for delivering functional starting libraries for a set of ten whole-cell-SELEX (Systematic Evolution of Ligands by Exponential Enrichment) processes. This epPCR method uses inosine to introduce targeted mutations, avoiding the need for commercial oligo pools or large-scale synthesis. We applied this method to a “universal aptamer” and subjected the three resulting libraries to two rounds of selection against ten diverse targets including probiotic and pathogenic bacteria (Gram-negative and -positive) as well as human cell lines. The enriched aptamers exhibited new binding specificities, demonstrating that the approach supports functional selection. Much like dusting off an old tool and finding it perfectly suited for a modern task, this work shows that revisiting established techniques can address current challenges in aptamer development. Our main finding is that epPCR provides a robust, cost-effective strategy for generating starting libraries and lowers the barrier for initiating successful SELEX campaigns.